2017
DOI: 10.17235/reed.2017.4219/2016
|View full text |Cite
|
Sign up to set email alerts
|

The utility of the macro-aggregated albumin lung perfusion scan in the diagnosis and prognosis of hepatopulmonary syndrome in cirrhotic patients candidates for liver transplantation

Abstract: The 99mTc-MAA is a low sensitivity test for the diagnosis of HPS that can be useful in patients who have concomitant lung disease and in severe to very severe cases of HPS. It was not related to mortality, and brain uptake normalized after LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This is in agreement with two previous studies which have shown a high prevalence of concomitant respiratory disease in 38.1% and 46.6% of HPS patients. 9,12 COPD was one of the most common co-existing respiratory disease.…”
Section: Concomitant Respiratory Disease (Yes Vs No)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with two previous studies which have shown a high prevalence of concomitant respiratory disease in 38.1% and 46.6% of HPS patients. 9,12 COPD was one of the most common co-existing respiratory disease.…”
Section: Concomitant Respiratory Disease (Yes Vs No)mentioning
confidence: 99%
“…9,10 Until now, less attention has been given to the presence of chronic intrinsic respiratory conditions which may coexist with HPS and may affect both preoperative and postoperative hypoxemia and outcome. 2,11,12 This study aimed to determine the outcome after LT in a cohort of patients with HPS with versus without concomitant respiratory disease.…”
Section: Introductionmentioning
confidence: 99%
“…The overall sensitivity of 99mTc-MAA in the diagnosis of HPS is 18.9% in all HPS cases, which is relatively low, but it is 66.7% in severe to very severe cases. Consequently, it can be used in patients with pulmonary disease and severe to very severe HPS (28).…”
Section: Progress In Technetium 99m-labeled Macroaggregated Albumin (Tc-mma) Dynamic Lung Perfusion Scan For the Diagnosis Of Hpsmentioning
confidence: 99%